2021
DOI: 10.1080/0886022x.2021.1880937
|View full text |Cite
|
Sign up to set email alerts
|

Iron, coronary artery calcification, and mortality in patients undergoing hemodialysis

Abstract: Objective: A high coronary artery calcification score (CACS) may be associated with high mortality in patients undergoing hemodialysis (HD). Recently, effects of iron on vascular smooth muscle cell calcification have been described. We aimed to investigate the relationships between iron, CACS, and mortality in HD patients. Methods: We studied 173 consecutive patients who were undergoing maintenance HD. Laboratory data and Agatston's CACS were obtained at baseline for two groups of patients: those with CACS !40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Many previous studies found that iron was closely related to vascular calcification (9). However, the results of the research are not consistent and may be related to different research settings (10).…”
Section: Introductionmentioning
confidence: 78%
“…Many previous studies found that iron was closely related to vascular calcification (9). However, the results of the research are not consistent and may be related to different research settings (10).…”
Section: Introductionmentioning
confidence: 78%
“…Our findings are consistent with those of other researchers. Mizuiri et al (Mizuiri et al, 2021) PeerJ reviewing PDF | (2021:09:65335:3:0:NEW 13 May 2022)…”
Section: Discussionmentioning
confidence: 99%
“…Anemia caused by erythropoiesis-stimulating agent hyporesponsiveness is associated with a higher risk of all-cause mortality in ESKD patients as well [ 23 , 24 ]. Therefore, these findings suggest that anemia, arterial calcification, and mortality are associated with ESKD patients [ 25 ]. However, excessive iron intake induces reactive oxygen species formation and promotes the local formation of oxidized LDL and arteriosclerosis through the induction of macrophages; caution should be exercised in iron supplementation.…”
Section: Discussionmentioning
confidence: 99%